FLAVAN-3-OL IN VITRO CULTURE CAMELLIA SINENSIS CONTRIBUTIONS IN ORDER SUPPORT FUNCTIONAL FOOD (UPN VETERAN JAWA TIMUR, 2015)
Abstract Flavan-3-ol act as bioactive compounds from in vitro culture of Camellia sinensis plant can support the functional food. These compounds are bioactive because of it has a chemical structure that is rich in hydroxide groups so that it can be as functional food. However, flavan-3-ol which is extracted from the fields stunted harvest wait time of up to 3-5 years. To overcome obstacles waiting time of harvesting of the land should be developed mode of production flavan-3-ol via in vitro culture. The purpose of this paper is to obtain the production of flavan-3-ol becoming more efficient. The process of production to achieve these objectives are: (1) initiation of callus, (2) sub callus, (3) the initiation of suspension culture, (4) extraction suspense culture, (3) Analysis of qualitative / quantitative compound of flavan-3-ol. Results of this study in the form of biomass culture can play a role in supporting both as a functional food additives, flavor and mix of food raw materials. Keywords: flavan-3-ol, Camellia sinensis, in vitro culture, functional food Abstrak Flavan-3-ol bertindak sebagai senyawa bioaktif dari kultur in vitro dari tanaman Camellia sinensis dapat berperan sebagai makanan fungsional. Senyawa bioaktif ini memiliki struktur kimia yang kaya kelompok hidroksida sehingga dapat menjadi makanan fungsional. Namun, flavan-3-ol yang dapat diekstrak terhambat panen menunggu hingga 3-5 tahun. Untuk mengatasi kendala waktu panen maka dilakukan produksi flavan-3-ol yang dikembangkan melalui kultur in vitro. Tujuan dari makalah ini adalah untuk mendapatkan produksi flavan-3-ol menjadi lebih efisien. Proses produksi untuk mencapai tujuan tersebut adalah: (1) inisiasi kalus, (2) sub kalus, (3) inisiasi kultur suspensi, (4) budaya ketegangan ekstraksi, (3) Analisis kualitatif / kuantitatif senyawa flavan -3-ol. Hasil penelitian ini dalam bentuk biomassa dapat berperan sebagai aditif makanan fungsional, flavor dan campuran bahan baku makanan. Kata kunci: flavan-3-ol, Camellia sinensis, kultur in vitro, makanan fungsional